A systematic review of the use of virtual reality in teaching Chinese as a foreign language - Liu, Weiming (Journal of China Computer-Assisted Language Learning, 2025)
The purpose of this review is to provide a thorough analysis of existing research on the implementation of virtual reality (VR) in teaching Chinese as a foreign language (TCFL). In recent years, there has been a growing interest in the potential benefits of VR for language learning, and multiple studies have explored its application in TCFL. However, to date, no systematic reviews on the specific uses of VR in TCFL have been conducted. This study aims to bridge this gap by conducting a comprehensive review of empirical articles on the topic, identified from the Scopus and Web of Science databases. The search terms include “VR”, “virtual reality”, and “Chinese language”. The findings of this review shed light on the current trends in VR-related publications in the field of TCFL, the research settings where VR is used to support learning, and the potential benefits and effectiveness of VR in enhancing Chinese language learning, such as linguistic growth, communication skills, motivation, and immersive and authentic learning contexts. The review also highlights the challenges and limitations of using this technology in TCFL. The significance of this review lies in its potential to inform educators, researchers, and practitioners interested in using VR in TCFL about the current state of research and its implications for language learning. It can also contribute to the development of best practices for the effective use of VR in TCFL, ultimately leading to improved language learning outcomes for students.